2020
DOI: 10.1111/ibi.12843
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for intraspecific phenotypic variation in songbirds along elevation gradients in central Europe

Abstract: Studying phenotypic variations along gradients may provide insights into mechanisms that drive species distributions and thus can be useful indicators of environmental change. In mountains, the study of phenotypic variation along elevation gradients is of increasing relevance due to the impacts of climate change. We analysed European ringing data to measure the direction of phenotypic variation along elevation gradients in six common, resident songbird species occurring along a wide elevational range. We model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This predicts that small-bodied birds should show a stronger response to cold temperatures, in this case higher elevation, than large birds which may be better able to withstand cooler temperatures. Although evidence for within-species variation in body size along the elevational gradient to offset constraints of cold-stress is scant for birds (Freeman 2017, Sander andChamberlain 2020), we found that thermo-insulative feather structure was significantly driven by body size. The weak association between relative feather length and elevation (Fig.…”
mentioning
confidence: 48%
“…This predicts that small-bodied birds should show a stronger response to cold temperatures, in this case higher elevation, than large birds which may be better able to withstand cooler temperatures. Although evidence for within-species variation in body size along the elevational gradient to offset constraints of cold-stress is scant for birds (Freeman 2017, Sander andChamberlain 2020), we found that thermo-insulative feather structure was significantly driven by body size. The weak association between relative feather length and elevation (Fig.…”
mentioning
confidence: 48%
“…1, 2A). Increasing evidence supports that the environmental heterogeneity caused by orography produces altitudinal displacements whose effects on bird biology have often been overlooked (Boyle et al 2016, Boyle 2017, Sander and Chamberlain 2020. These movements could strongly affect the moult of the Eurasian blackcap populations, a partially migratory species in which migratory and sedentary individuals can coexist in a small geographical area (Chapman et al 2011).…”
Section: Articlementioning
confidence: 99%
“…wing size) are related to individual quality and thus, fitness (Mérő et al 2020). While studies considering habitat characteristics like vegetation/land cover in relation to wing morphology are very scarce, the influence of elevation has been more intensively investigated, mostly in relation to wing length (Laiolo and Rolando 2001, Lu et al 2009, Wilson et al 2010, Boyce et al 2019, Sander and Chamberlain 2020). These studies have given partly contrasting results, often indicating the lack of elevational patterns, or a positive wing length–elevation relationship in different studies/species.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have given partly contrasting results, often indicating the lack of elevational patterns, or a positive wing length–elevation relationship in different studies/species. Such cases of positive relationships could be interpreted as a need for a more efficient flight in conditions of lower air pressure and higher hypoxia risk associated with higher elevations (Sander and Chamberlain 2020). While these studies provided extremely valuable information, the lack of consideration of other environmental factors in addition to elevation, such as vegetation or land cover, complicates interpretation.…”
Section: Introductionmentioning
confidence: 99%